2017
DOI: 10.1080/13880209.2017.1400077
|View full text |Cite
|
Sign up to set email alerts
|

Production of eurycomanone from cell suspension culture of Eurycoma longifolia

Abstract: Context: Eurycomanone is found in the Eurycoma longifolia Jack (Simaroubaceae) tree, exhibits significant antimalarial activity, improves spermatogenesis, suppresses expression of lung cancer cell tumour markers and regulates signalling pathways involved in proliferation, cell death and inflammation.Objectives: Establishment of cell suspension culture of E. longifolia to determine the eurycomanone accumulation during cultures.Materials and methods: Callus of E. longifolia was cultured in MS medium supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…presented a trend associated with its growth, reaching a maximum yield during the exponential phase and, subsequently, decreasing rapidly due to the lack of nutrients and consequent cellular death [ 32 ]. In another species, Eurycoma longifolia , it was reported that cell suspension cultures produce the quassinoid eurycomanone; this also occurs from the beginning of the growth kinetics, reaching a maximum amount of 1.7-mg g −1 DW [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…presented a trend associated with its growth, reaching a maximum yield during the exponential phase and, subsequently, decreasing rapidly due to the lack of nutrients and consequent cellular death [ 32 ]. In another species, Eurycoma longifolia , it was reported that cell suspension cultures produce the quassinoid eurycomanone; this also occurs from the beginning of the growth kinetics, reaching a maximum amount of 1.7-mg g −1 DW [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the validation of the authenticity of the HMPs, only those HMPs which were identified as either authentic or substituted using DNA barcoding are the ones further analysed using this method. So also, the validation was based on the presence of eurycomanone marker which is one of the most important and abundant bioactive compound present in this plant (Nhan and Loc 2017 ). The eurycomanone standard showed a peak area with a retention time of 2.854 min similar to that of root extract 2.839 and three tested HMPs (TAP-1, TAP-3 and TAP-8).…”
Section: Resultsmentioning
confidence: 99%
“…Eurycoma longifolia Jack (Simaroubaceae) commonly known as Tongkat Ali, is found in Southern Asian countries such as Malaysia, Indonesia, Vietnam, Myanmar, Cambodia and Thailand. E. longifolia extracts (particularly roots) have been reported to display a wide range of therapeutic properties such as antimicrobial, antimalarial, antidiabetic, antiulcer, cytotoxicity against cancerous cells (Bhat and Karim 2010 ; Nhan and Loc 2017 ) but the most famous is for aphrodisiac activities (Ismail et al. 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different concentrations of YE (20-250 mg/L), MeJA (10-500 µM) and SA (10-500 µM) were used to investigate their influences on cell growth and eurycomanone accumulation after 14 days of culture. In a previous report, we established the profile of E. longifolia cell growth with a maximum biomass obtained on day 14 (Nhan and Loc 2017). Therefore in present work, the effects of elicitors on in vitro cultures will be evaluated at this time.…”
Section: Effect Of Elicitor Concentrationmentioning
confidence: 99%